Progressive damage analysis of composite layered plates using a mesh reduction method - Zahari, Rizal; El Zafrany, Ahmed (Federation of Engineering Institutions of Islamic Countries, 2006)
A mesh reduced method (finite strip method), for non-linear stress analysis based on the tangential stiffness matrix has been developed using the new concept of polynomial finite strip elements, with Mindlin plate bending theory for composite plates. A progressive damage methodology and algorithm for composite laminates was successfully developed for the new finite strip methods using stress-based failure criteria. A finite strip analysis programming package which is capable of performing non-linear progressive damage analysis for composite plates has also been developed with Mindlin plate bending element. Validation of the developed finite strip package has been successfully carried out by comparing the results with corresponding results obtained with the finite element analysis using ABAQUS and with some published experimental results. Good comparisons with the finite element results and experimental results were observed through various test cases, confirming the accuracy and reliability of the new derivations and the programming package.